Scar Endometriosis Following Cesarean Section - Rüya Deveer; Melike Doğanay; Esma Sarıkaya; Alper Başbuğ; Derya Başbuğ; Levent Şırvan; Leyla Mollamahmutoğlu (Medical Network, 2012)
OBJECTIVE: The purpose of our study was to evaluate clinical features of abdominal wall endometriosis following cesarean section. STUDY DESIGN: Our institution's database over a 5-year period was performed, yielding 9 surgically proven cases of abdominal wall endometriosis that were retrospectively studied. All patients had undergone sonography. The clinical data were analyzed. RESULTS: All patients had a history of at least one prior cesarean section. None of them had endometriosis history. All presented with focal pain near the surgical scar, which was cyclic in seven patients. Three patients presented with a palpable mass near the scar. Sonography detected all lesions within the abdominal wall, with a mean diameter of 30 mm. All lesions were vascular, and solid, with some cystic changes. CONCLUSION: Abdominal wall endometriosis frequently presents with cyclical pain during menstruation which is localised to a palpable mass in the abdominal wall especially in those who have had previous cesarean section. Complete surgical excision is curative.